2021
DOI: 10.1155/2021/1396326
|View full text |Cite
|
Sign up to set email alerts
|

The Automatic Detection of Pedestrians under the High-Density Conditions by Deep Learning Techniques

Abstract: The automatic detection and tracking of pedestrians under high-density conditions is a challenging task for both computer vision fields and pedestrian flow studies. Collecting pedestrian data is a fundamental task for the modeling and practical implementations of crowd management. Although there are many methods for detecting pedestrians, they may not be easily adopted in the high-density situations. Therefore, we utilized one emerging method based on the deep learning algorithm. Based on the top-view video da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…This method allows for continuous tracking of a large number of pedestrians using a multi-objective tracker, which facilitates the analysis of individual or group behaviour patterns ( Cao, Sai & Lu, 2020 ). It has been experimentally demonstrated that nearly 1,000 people can be continuously and dynamically identified using deep learning ( Xue & Ju, 2021 ), and the accuracy may be greater than 0.95, even for a pedestrian density of 9.0 per m 2 ( Jin et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…This method allows for continuous tracking of a large number of pedestrians using a multi-objective tracker, which facilitates the analysis of individual or group behaviour patterns ( Cao, Sai & Lu, 2020 ). It has been experimentally demonstrated that nearly 1,000 people can be continuously and dynamically identified using deep learning ( Xue & Ju, 2021 ), and the accuracy may be greater than 0.95, even for a pedestrian density of 9.0 per m 2 ( Jin et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, this paper mainly studies the description language of common business models, and then introduces knowledge engineering technology into the modeling and analysis of multi-objective problems, and puts forward the corresponding intelligent model description language and algorithm generation method. [4][5][6]…”
Section: Introducementioning
confidence: 99%
“…The experimental results show that the average precisions for pedestrian and vehicle detection improved by 2%∼5% compared with YOLOv3 model. Jin et al [ 11 ] utilized one emerging method based on YOLOv3 in high-density pedestrians detection situations and achieved good results. To improve the near-surface detection performance of UAVs in low illumination environments, Wang et al [ 12 ] proposed a U-type generative adversarial network (GAN) to fuse visible and IR images to generate color fusion images.…”
Section: Introductionmentioning
confidence: 99%